O papel de um grupo colaborativo no desenvolvimento profissional docente de professoras dos anos iniciais - Fonseca, Celestina Cruz Pedroni (2022)
This dissertation was developed in a collaborative group with teachers from the early years of a municipal school in Sorocaba/SP, in the years 2020 to 2021. This research aims to verify the reflection on the collaborative culture, breaking with professional isolation by facilitating a space to disseminate this process, having the teacher as the protagonist to identify their training needs for their professional development. We use two devices to locate and analyze how a collaborative group is formed and constituted; we aim, therefore, to map the collaborative profiles found in this group and to establish the characteristics that facilitate the process, as well as to identify the dimensions of professional development experienced by these professors, that is, the profiles and collaborative stages of the professors based on their interactions whose background background was to discuss the implementation of scientific literacy in the classroom in the early years. The methodological approach was the participatory research, during two semesters, organized in 18 virtual meetings, all recorded and transcribed for the organization of the analysis categories that, initially, point out collaborative and engagement profiles within the group, indicating that the group training proposal collaborative approach has provided teachers with the challenge of reflecting the teaching culture, their own praxis and the process of professional development of teachers. Thus, we intend to point out how a collaborative group, properly constituted, can be an enriching tool capable of stimulating thinking, acting and solving problems, of creating perspectives of successful experiences related to the pedagogical routine, favoring reflection and change of praxis through collaborative culture.